(untitled) (Temas de Nuestra América Revista de Estudios Latinoaméricanos, 2025)
Democracy, alongside free and competitive electoral processes, essentially, implies the respect of fundamental rights. This paper reflects on the impact that a growing phenomenon in Latin America that consists of the use of emergency regimes to face violence and organized crime. This is understood as an exacerbation of the so-called tough in crime policies or punitive populism. According to some international organizations, the flexibilization of constitutional guarantees on behalf of security, is bringing, at the same time, the violation of human rights and a weakening of the Rule of Law. From this, a big question emerges regarding to the quality and future of democracies in our region.